Clinical and experimental substantiation of the use of Vivaderm in the treatment of skin diseases in animals - Kyrychko, B.; Shepel, K.; Peredera, R. (Scientific Progress & Innovations, 2025)
Skin diseases are quite common among small livestock. For their treatment, a huge arsenal of local, systemic and complex medicines is offered, which is constantly being replenished. Therefore, the aim of the study was to investigate the clinical efficacy of Vivaderm in the treatment of skin diseases in animals in a comparative aspect. The experiments involved white rats with allergic eczematous dermatitis reproduced by sensitisation with phenylhydrazine and dogs with clinical signs of eczema, dermatitis, and superficial pyoderma. The animals were treated with Vivaderm by daily double-daily applications until clinical signs disappeared and the affected skin areas recovered. The objective criteria for clinical efficacy were the disappearance of signs of the disease, recovery of the affected skin areas and positive dynamics of blood biochemical parameters. It was found that phenylhydrazine-induced dermatitis in rats is characterised by signs of inflammation and skin necrosis. The use of Vivaderm ointment allowed for a reduction in the lesion area and a significant decrease in the inflammatory reaction by the seventh day. Complete recovery of skin structures and hair occurred by the 18 day. Consistent application of Vivaderm ointment to sick dogs allowed to influence the main clinical manifestations of skin diseases – hyperaemia, exudation, itching. The disappearance of these clinical signs occurred within 3.2–5.3 days and was significantly different from the results obtained with the use of the comparison drug. Complete recuperation and restoration of the affected skin areas occurred by 7.8 days, which is 1.3 times faster than with the comparison drug. The use of Vivaderm contributed to a significant decrease in the activity of alanine aminotransferase and alkaline phosphatase. At the same time, the levels of total protein, glucose, bilirubin, cholesterol, cholesterol, urea, creatinine, and aspartate aminotransferase activity did not have significant fluctuations throughout the treatment period. Thus, the consistent use of Vivaderm in the treatment of skin diseases in animals allows to achieve a stable clinical recovery in a relatively short time.